Diagnostic performance of individual characteristics and anthropometric measurements in detecting elevated serum alanine aminotransferase among children and adolescents - Yu-Lan Ou; Yue-Rong Lai; Chao-Nan Jiang; Jing Zhang; Zan Ding (BMC, 2020)
Abstract Background Screening for elevated serum alanine aminotransferase (ALAT) can help identifying individuals at the risks of chronic and metabolic diseases, but blood collection is invasive and cannot be widely used for investigations. Considered as simple and inexpensive screening indices, individual characteristics and anthropometric measurements can be measured in a large crowd and may be important surrogate markers for ALAT levels. This study aimed to examine the diagnostic performance of individual characteristics and anthropometric parameters as predictive factors for discerning an elevated ALAT activity among Shenzhen children and adolescents. Methods A school-based screening study was performed from 9 high schools in Shenzhen during February 2017 and June 2018. Receiver operating characteristic curve was used to examine the diagnostic performance of each variable for detecting elevated ALAT. Results Altogether 7271 students aged 9-17 years were involved. The proportion of elevated ALAT greatly increased with increasing classification of BMI-z. By the sex-specific cut-offs for elevated ALAT (30 U/L boys; 19 U/L girls), BMI showed the highest area under the curve of 0.789 (95% CI 0.765-0.812) and followed by weight (0.779 [0.755-0.802]), BMI-z (0.747 [0.722-0.772]), height (0.622 [0.597-0.647]), and age (0.608 [0.584-0.632]), while height-z was not capable. With the cut-off of 67.8 kg for weight and 22.6 kg/m2 for BMI, the accuracy to identify elevated ALAT was 87.1% for weight and 82.9% for BMI. Conclusions The presence of elevated ALAT was more common in overweight or obese children and adolescents. BMI and weight had the superiority of detecting elevated ALAT, followed by BMI-z, height, and age.